THE ANALYSIS OF FACTORS AFFECTING THE CAPITAL STRUCTURE ON LISTED MINING COMPANIES IN INDONESIA STOCK EXCHANGE - Charaka M Nandatama; Sulastri Sulastri; Taufik Taufik (JEMBATAN, 2018)
The objectives of this research are to examine the effect of Assets Growth,Likuidity, Assets Structure, and Sales Growth influence simoultaneously and partiallyon Capital Structure. Research conducted at mining companies that listed on IndonesiaStock Exchange period 2012- 2015. The research population was 41 companies, with thesample of 14 companies with sampling using purposive sampling technique. Theanalytical method used is multiple linear regression analysis, which previously testedwith the classical assumption.The result showed that the Assets Growth, Likuidity, Assets Structure and SalesGrowth influence simultaneous on the Capital Structure. The research also revealedthat, Assets Growth, Likuidity, Assets Structure and Sales Growth influence partiallynegative significant on the Capital Strucuture. On the other hand, R-Square valueamnounted at 32.6%, its mean that 32,6% movement of Capital Structure can bepredicted from the movement of the four independent variables.Keywords : capital structure, assets growth, likuidity, assets structure, sales growth